2002
DOI: 10.1002/aoc.313
|View full text |Cite
|
Sign up to set email alerts
|

Organotin levels in the Ria Formosa lagoon, Portugal

Abstract: Organotin concentrations were measured in water, sediments and clams (Ruditapes decussatus) from 11 sites in the Ria Formosa lagoon, Portugal, in 1992±93. Results showed a marked spatial pattern of tributyltin (TBT) and dibutyltin concentrations. The highest organotin concentrations were observed at Olha Äo (site 5), where the most important fishing harbour of the Southern coast of Portugal is located.Results indicated that fishing vessels, moored in the harbour at Olha Äo (site 5), were the major source of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…manly TBT) and polychlorinated byphenyls (PCBs) have been detected in M. galloprovincialis and R. decussatus as well as in water and sediments collected in the Lagoon (Table 1). The results of endocrine disruption and oxidative stress in this study reflect the results obtained in other studies on the presence of different contaminants in Ria Formosa waters, as well as the complex interactions between them (Coelho et al 2002, Bebianno and Serafim 2003, Barreira et al 2005, Díez et al 2005, Barreira et al 2007, Cravo et al 2009). The two determined biomarkers are not specific to a particular group of contaminants but could represent an integrated response to the impact of multiple toxic and/or environmental factors (Lafontaine et al 2000).…”
Section: Mytilus Galloprovincialissupporting
confidence: 89%
“…manly TBT) and polychlorinated byphenyls (PCBs) have been detected in M. galloprovincialis and R. decussatus as well as in water and sediments collected in the Lagoon (Table 1). The results of endocrine disruption and oxidative stress in this study reflect the results obtained in other studies on the presence of different contaminants in Ria Formosa waters, as well as the complex interactions between them (Coelho et al 2002, Bebianno and Serafim 2003, Barreira et al 2005, Díez et al 2005, Barreira et al 2007, Cravo et al 2009). The two determined biomarkers are not specific to a particular group of contaminants but could represent an integrated response to the impact of multiple toxic and/or environmental factors (Lafontaine et al 2000).…”
Section: Mytilus Galloprovincialissupporting
confidence: 89%
“…However, in this task, we faced some limitations as follows: (a) values of BTs from Diez et al (2005) had to be extrapolated from a graphical representation; (b) in Coelho et al (2002), a few different values for the same sample were presented in the text and in a graphical representation, being impossible to know which of them were accurate; (c) in Almeida et al (2007), explicit sampling sites at each studied area have not been reported. In addition, total absence of previous available data prevented any comparison for Cávado River and Ave River estuaries.…”
Section: Resultsmentioning
confidence: 99%
“…From 2001 to 2003, TBT and DBT have been analyzed in sediment samples of eight Portuguese estuaries (Almeida et al 2007). More localized works have been carried out at Tagus estuary in 1990 and 2000 (De Bettencourt et al 1999;Nogueira et al 2003), Ria Formosa in 1992/1993(Coelho et al 2002, and Ria de Aveiro in 2005 (Sousa et al 2007). In addition, indirect evidence of BT contamination of Portuguese sediments, obtained through imposex levels, has been reported for: Sado and Mira estuaries (sampling between 1993 and1998;Pessoa et al 2001), several sites in Portuguese coastwise (sampling in 2000;Barroso and Moreira 2002), Oporto coast (sampling in 1998; Santos et al 2004), and Ria de Aveiro (sampling between 2002Rato et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Trisubstituted OTC, including TBT and TPhT, are among the most hazardous pollutants to enter aquatic ecosystems (Hoch 2001 EC 2000). Although OTC were intensively investigated in the marine environment (Coelho et al 2002;Díez et al 2005;Godoi et al 2003;Gomez-Ariza et al 2001;Harino et al 1999;Milivojevič Nemanič et al 2002Ščančar et al 2007), they are a rare subject of research in river sediments (Bancon-Montigny et al 2004;ICPDR 2002;Lacorte et al 2006;Scrimshaw et al 2005).…”
mentioning
confidence: 99%